Upaya Meningkatkan Moral Peserta Didik Melalui Media POP UP Pintar Di Sekolah Dasar - Dinda Velita Bela; Natus Susilawati; Isnaini Niken Sholehah; Suyitno . (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2020)
The purpose of writing scientific papers is to improve the morale of the nation's future generations by presenting pop-up media that can help educators to teach moral education to students in elementary schools. This writing uses the literary study method, which is the technique of collecting data by conducting study studies of books, literature, notes, and reports that are related to the problem being solved. The result of his study is that smart pop up media is a solution to increasing the morale of students in elementary schools. In this study, it can be concluded that smart pop up media can be used as a medium for increasing morale in elementary schools. This Smart Pop Up Media is very interesting and unique. Children prefer new things that they have never met before. The author's Pop Up media is also different from the popular Pop Up media. Most of the existing Pop Up media only present images. Here the author presents Pop Up media with text and images and will also be added coded to be linked to the YouTube channel so that children can also watch explanations in video form. Not only that, what distinguishes writer media from existing media on the market, our media also takes the theme of togetherness which we will later integrate with Indonesian culture so that students can appreciate the differences that exist.